Interlayer resonant Raman modes in few-layer MoS2 - Scheuschner, Nils; Gillen, Roland; Staiger, Matthias; Maultzsch, Janina (Physical Review B, 2015)
We report two first-order Raman modes in the spectra of few-layer MoS2 at 286 and 471 cm(-1) that are only observed at excitation energies above 2.4 eV. We show that these normally not observed modes are interlayer modes related to symmetry-forbidden modes of the single layer. Based on group theory, we provide a general treatment and systematic classification of all phonon modes in few-layer crystals with inversion symmetry and/ or horizontal reflection symmetry. The results can thus be applied to different materials like few-layer graphene, transition-metal dichalcogenides, or BN. Moreover, the few-layer specific Raman modes are strongly resonant with the C optical transition in MoS2. We conclude that the corresponding exciton wave function is extended over all layers of the few-layer MoS2, in contrast to the A and B exciton